Arte Rupestre no Alentejo Central: o caso de Arraiolos - ROCHA, Leonor (2015)
The rock art of Central Alentejo known became internationally in the early twentieth century, with the work carried out in the Cities of Mora and Arraiolos, by V. Correia (Correia 1921). During the work excavation that was occurring in Pavia, V. Correia made some archaeological sites identification work, including a set of rock art outdoors, municipality of Arraiolos - two granite outcrops, with engravings (essentially anthropomorphic and cruciform) on vertical surfaces. The work carried out in the past few years allowed us to identify other sites with rock art, particularly in megalithic monuments and granite outcrops, in different types of landscapes. In this communication go will bead dress the question of space and place, the type of art and also of their state of conservation.